Discrete Anatomical Coordinates for Speech Production and Synthesis - Assaneo, M. Florencia; Ramirez Butavand, Daniela; Trevisan, Marcos A.; Mindlin, Gabriel B. (Frontiers in Communication, 2019)
The sounds of all languages are described by a finite set of symbols, which are extracted from the continuum of sounds produced by the vocal organ. How the discrete phonemic identity is encoded in the continuous movements producing speech remains an open question for the experimental phonology. In this work, this question is assessed by using Hall-effect transducers and magnets -mounted on the tongue, lips and jaw- to track the kinematics of the oral tract during the vocalization of vowel-consonant-vowel structures. Using a threshold strategy, the time traces of the transducers were converted into discrete motor coordinates unambiguously associated with the vocalized phonemes. Furthermore, the signals of the transducers combined with the discretization strategy were used to drive a low-dimensional vocal model capable of synthesizing intelligible speech. The current work not only assesses a relevant inquiry of the biology of language, but also demonstrates the performance of the experimental technique to monitor the displacement of the main articulators of the vocal tract while speaking. This novel electronic device represents an economic and portable option to the standard systems used to study the vocal tract movements.